2012
DOI: 10.3109/10428194.2012.743657
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second malignant neoplasms after cyclophosphamide-based chemotherapy with or without radiotherapy for non-Hodgkin lymphoma

Abstract: Relatively little information is available on quantitative risks of therapy-induced second malignant neoplasm (SMN) in patients with non-Hodgkin lymphoma (NHL). A nested case-control study was conducted in a cohort of 3412 patients treated for NHL between 1990 and 2006, including 118 patients with SMN and 472 controls. Risks of leukemia/lung/breast/colorectal and bladder cancer were higher in NHL compared with the general population. A higher risk of leukemia was restricted to patients given a cumulative dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…There is emerging evidence that regulatory B cells are the main mediators of this mechanism 30. In humans, the hypothesis that rituximab enhances the antitumour immune response is supported by the trend towards a lower risk of developing a second primary malignancy in patients with non-Hodgkin's lymphoma treated with rituximab-containing chemotherapy compared with patients treated with chemotherapy that does not include rituximab 31 32. However, clarification of the effects of B-cell depletion on antitumour immunity in humans requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that regulatory B cells are the main mediators of this mechanism 30. In humans, the hypothesis that rituximab enhances the antitumour immune response is supported by the trend towards a lower risk of developing a second primary malignancy in patients with non-Hodgkin's lymphoma treated with rituximab-containing chemotherapy compared with patients treated with chemotherapy that does not include rituximab 31 32. However, clarification of the effects of B-cell depletion on antitumour immunity in humans requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4,13 ] Cyclophosphamide is known to have weaker carcinogenicity compared to other alkylating agents however high dose cyclophosphamide based therapies increases the risk of second cancers in patients with CLL and Non-Hodgkin’s lymphoma. [ 14,15 ] Skin cancers which developed after therapy with fludarabine in patients with CLL were reported to be more aggressive, with higher growth rate, recurrence and distant metastasis. [ 16 ] Cheson et al compared the number of observed to the expected second cancers in 724 relapsed refractory patients with CLL who were treated with fludarabine for a median follow up of 7.4 years.…”
Section: Introductionmentioning
confidence: 99%
“…There has been conflicting data whether radiotherapy adds to the leukemia risk associated with chemotherapy in patients treated with combined modality treatment. In non-Hodgkin lymphoma, there was no correlation between radiation and risk of developing leukemia [32].…”
Section: Epidemiology Of T-mds After Therapeutic Radiation Exposurementioning
confidence: 98%
“…T-AML/ MDS was a major contributor to the increased risk of second cancers in these patients compared to the general population [57]. In NHL, a cumulative dose of cyclophosphamide of 11,250 mg/m2 or higher was associated with increased risk of t-MDS/AML compared to a matched NHL cohort (odds ratio: 7) [32].…”
Section: Epidemiology Of T-mds After Chemotherapy Exposurementioning
confidence: 99%